Relationship between maternal–infant gut microbiota and infant food allergy - Wang, Shuo; Zhang, Rui; Li, Xinyue; Gao, Yajuan; Dai, Nini; Wei, Yuan; Liu, Luyan; Xing, Yan; Li, Zailing (Frontiers in Microbiology, 2022)
The gut microbiota plays a crucial role in food allergies. We sought to identify characteristics of the maternal gut microbiota in the third trimester and the infant gut microbiota in early life and the association of these microbiotas with infant food allergy. A total of 68 healthy pregnant women and their full-term newborns were selected from a cohort of 202 mother–infant pairs; among them, 24 infants had been diagnosed with food allergy within 1 year of age, whereas 44 infants were healthy without allergic symptoms. We collected 65 maternal fecal samples before delivery and 253 infant fecal samples at five time points following birth. Fecal samples were microbiologically analyzed using 16S rRNA gene sequencing. Holdemania abundance in the maternal gut microbiota in the third trimester was significantly higher in the non-allergy group than in the food allergy group (P=0.036). In the infant gut microbiota, Holdemania was only found in meconium samples; its abundance did not differ significantly between the two groups. The change in the abundance of Actinobacteria over time differed between the non-allergy and food allergy groups (FA, P=0.013; NA, P=9.8×10-5), and the change in the abundance of Firmicutes over time differed significantly in the non-allergy group (P=0.023). The abundances of genera Anaerotruncus, Roseburia, Ruminococcus, and Erysipelotricaceae were significantly different between the non-allergy and food allergy groups at different time points. Our results showed that maternal carriage of Holdemania during the third trimester strongly predicted the absence of food allergies in infants; there was no correlation between the presence of food allergies and the abundance of Holdemania in the infant gut microbiota. More dynamic fluctuations in phyla Actinobacteria and Firmicutes early in life protect against food allergy. Thus, the enrichment of the infant gut microbiota early in life with short-chain fatty acid-producing bacteria may be beneficial in preventing the development of food allergies in infants.